Corrigendum to ''The relative roles of CO2 and palaeogeography in determining late Miocene climate: results from a terrestrial model-data comparison'' published in Clim. Past, 8, 1257–1285, 2012 - A. M. Haywood; J. T. Eronen; M. J. Pound; U. Salzmann; R. Flecker; D. J. Lunt; C. D. Bradshaw (Climate of the Past, 2012)
No abstract available.